The Challenge of Exploiting ABCG2 in the Clinic - Robey, Robert W. (2011)
ABCG2, or breast cancer resistance protein (BCRP), is an ATP-binding cassette half transporter that has been shown to transport a wide range of substrates including chemotherapeutics, antivirals, antibiotics and flavonoids. Given its wide range of substrates, much work has been dedicated to developing ABCG2 as a clinical target. But where can we intervene clinically and how can we avoid the mistakes made in past clinical trials targeting P-glycoprotein? This review will summarize the normal tissue distribution, cancer tissue expression, substrates and inhibitors of ABCG2, and highlight the challenges presented in exploiting ABCG2 in the clinic. We discuss the possibility of inhibiting ABCG2, so as to increase oral bioavailability or increase drug penetration into sanctuary sites, especially the central nervous system; and at the other end of the spectrum, the possibility of improving ABCG2 function, in the case of gout caused by a single nucleotide polymphism. Together, these aspects of ABCG2/BCRP make the protein a target of continuing interest for oncologists, biologists, and pharmacologists.